Gartland type III supracondylar humerus fractures: Outcome and complications as related to operative timing and pin configuration. (December 2014) - Abbott, Matthew D.; Buchler, Lucas; Loder, Randall T.; Caltoum, Christine B.
Purpose: Supracondylar fractures of the humerus are the most common fracture of the elbow in children. The purpose of this study was to evaluate, in terms of outcomes and complications, Gartland type III pediatric supracondylar humerus fractures treated at a pediatric level-one trauma center over a 7-year period, specifically addressing the impact of time to surgery on the incidence of complications and conversion to open reduction. Methods: We retrospectively reviewed 297 pediatric patients that sustained a closed Gartland type III supracondylar humerus fracture treated between December 2004 and December 2011. The time to the operating room was calculated from the medical records for each patient. The outcome measures evaluated were operative time, conversion to open procedure, and perioperative and postoperative complications. Results: In our study, there were 30 complications in 25 children (8.4%). Conversion to open reduction occurred in 28 children (9.4%). The time from the emergency department to the operating room was not significantly correlated with increased complications, increased operative time, or conversion to open reduction ( p > 0.05). Crossed pinning resulted in an increased risk of overall complications [odds ratio (OR) = 2.6] and iatrogenic nerve injuries (OR = 9.3). Complications also occurred more commonly in boys (OR = 3.3) and in older patients ( p = 0.0069) Conclusions: We found no significant correlation between the time to surgery and complications, operative time, or need for open reduction. These findings support the trend of treating Gartland type III supracondylar humerus fractures in a less urgent manner. In addition, our study supports the concept that cross pinning leads to more complications than lateral pinning, including an 8-fold increase in iatrogenic nerve injury.